PERCEPTION OF CLIENTS OF GYMNASTICS ACADEMIES IN RELATION TO THE PHYSICAL EDUCATION PROFESSIONAL (Fiep Bulletin - online, 2019)
The physical education professional has become a service provider, considering that in the current society the cultureof the body is expressed increasingly strong in the multiple issues inherent to it, thus being extremely important that theprofessionals are Qualified to provide a quality service, since this product will return customer satisfaction, consequently its futureprofessional in this area depended on this relationship. The objective of this work was to establish the level of customersatisfaction of gym academies in relation to physical education professionals. The present study presents a transversal characterwith a quantitative approach. 60 volunteers participated in this study. To obtain the results was used an online questionnairedeveloped through a tool of Google Docs. The questionnaire was elaborated with the purpose of addressing issues inherent inthe practice of physical exercises in gym academies and satisfaction with the physical education professional. The group inquestion expressed a higher percentage satisfied with the results achieved, the largest percentiles were also established for theaspects inherent to the performance of the physical education professional. It is concluded that the clients are satisfied with theperformance of the physical education professional, a reflection of satisfaction in relation to the successful goals.
Keywords: Physical Education Professional; Satisfaction